SEJARAH DAN PERKEMBANGAN KEHIDUPAN SUKU ANAK DALAM KABUPATEN MERANGIN PROVINSI JAMBI (2011-2019) - Fikri Surya Pratama; Arki Aulia Hadi (Jurusan Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2022)
This article aims to explain how the development of the life of the Anak Dalam Tribe in Mentawak Village, Nalo Tantan District, Merangin Regency, Jambi Province after being empowered in 2011. The Suku Anak Dalam group in Mentawak Village was chosen as the object of research because they are one of the three residential areas of the Tribal group. Anak Dalam in Merangin Regency who have been resettled and empowered by the local government. The results of the study show that the life of the group before being empowered by the Merangin Regency government experienced a very poor life, in addition to the condition of the forest where they lived which had started to shrink due to the cross-road construction project and the oil palm company project, they were also often involved in social conflicts, thus making them continue to live. move around while trying to maintain their lives and the values ​​of their cultural customs. After settling and being empowered in Mentawak land in 2011, their lives have progressed gradually, some residents already have houses, ID cards, KK, Jamkesda, education through informal schools by honorary teachers from the District Social Service. Merangin, however, for the problem of their work still depends on the results of hunting pigs, the development of skills and other skills has not been carried out properly.